Groundwater management strategy to reduce the impact of land degradation in tropical karst areas - Naufal, Muhammad; Adji, Tjahyo Nugroho; Haryono, Eko (Journal of Degraded and Mining Lands Management, 2025)
The study aimed to determine the level of pollution sensitivity associated with fertilization activities in agricultural land in two karst spring catchment areas (Beton and Guntur). The aquifer characteristics of these two springs differ; the Beton Spring has a more developed allogenic channel development, whereas the Guntur Spring has a less developed autogenic system. In this study, the COCKPIT-PLUS and Master Recession Curve (MRC) techniques are combined to define land use zoning and the degree of aquifer sensitivity to pollution. Field sampling and stakeholder interviews were also conducted to assess land management practices and pollutant concentrations in the springs. The results show that due to the influence of more intensive and varied land use, Beton Spring has a higher sensitivity to pollution, as evidenced by higher concentrations of nitrate, phosphate, and Escherichia coli. In contrast, lower pollution levels in Guntur Spring occur due to the narrower recharge zone area supported by a more consistent planting pattern. Various strategies, including vegetative restoration, drainage planning, land use regulation, and communicative education, were formulated using the DPSIR framework. Strategies are critical in areas with high sensitivity, such as the Beton and Jomblangan recharge zones, which also highlight the necessity of land use restrictions based on upstream-downstream interactions. This study emphasized the importance of adapting the protection plan for karst aquifer recharge zones in response to land use intensity and degradation. It proposes an evidence-based integrated management model that focuses on decreasing the effects of land degradation in tropical karst aquifer systems.